2012
DOI: 10.7226/jtfm.18.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Spacing and Genotype on Height and Diameter Growth of Four Eucalyptus Under Short Rotation

Abstract: In this paper, the dynamic change in tree height, diameter at breast height (dbh), and ground line diameter (gld) at different density was studied. Trial sites were established in Chepkoilel and Nangili areas of western Kenya. Eight tree species (2 hybrid eucalyptus clones; GC 10 and GC 167), 1 eucalyptus local landrace, 2 agroforestry (Grevillea robusta and Markhamia lutea), 1 pure eucalyptus (Eucalyptus grandis), and 2 preferred local species (Maesopsis eminii and Khaya nyasica) were planted on each site. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…On the other hand, ANOVA for randomised complete block design is used in most of the cases when species or genotype effect is tested together with spacing. A Nelder plot (Krinard, 1985;Waghorn et al, 2007;Kirongo et al, 2012) or a sector within the plot (Panetsos, 1980;Waghorn, Watt, 2013) is regarded as a replication (block) in such situations. Alternatively, ANOVA for splitplot design is applied in some cases, where "species mixture" is regarded as the main plot factor and "spacing" is viewed as the sub-plot effect (Wurtz, 1995;Doran et al, 2001).…”
Section: Methodological Approaches For Data Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, ANOVA for randomised complete block design is used in most of the cases when species or genotype effect is tested together with spacing. A Nelder plot (Krinard, 1985;Waghorn et al, 2007;Kirongo et al, 2012) or a sector within the plot (Panetsos, 1980;Waghorn, Watt, 2013) is regarded as a replication (block) in such situations. Alternatively, ANOVA for splitplot design is applied in some cases, where "species mixture" is regarded as the main plot factor and "spacing" is viewed as the sub-plot effect (Wurtz, 1995;Doran et al, 2001).…”
Section: Methodological Approaches For Data Analysesmentioning
confidence: 99%
“…Plant variables commonly studied are those related to growth and productivity: % survived plants, stem diameter (basal and breast-height), mid-stem girth, total height, basal area, stem volume, total and fractional biomass, leaf area (Decourt, Lemoine,. 1974;Delwaulle, 1979;Panestsos, 1980;Mark, 1983;Krinard, 1985;Reukema, Smith, 1987;Wurtz, 1995;Imada et al, 1997;Kerr, 2003;Aphalo, Rikala, 2006;Kirongo et al, 2012;Newton, 2015;Matos et al, 2015;Erkan, Aydin, 2016). Certain physiological parameters of growth, such as plant water potential, shoot photosynthetic potential, stomatal conductance and needle chemistry (Giordano, Hibbs, 1993;Doran et al, 2001), are addressed in some investigations, while other studies examine tree form and stem quality variables: height to the crown base, crown length, diameter and volume, height-diameter ratio, live crown ratio, stem and crown form, branchiness and epicormic branching, branch diameter, crown diameter to stem diameter ratio, internode length, relative bark thickness, wood density (Lemoine, 1980;Hummel, 2000;Ferrere et al, 2005;Waghorn et al, 2007;Newton et al, 2012;Kuehne et al, 2013).…”
Section: Design Applications In the Forest Studiesmentioning
confidence: 99%
“…Os resultados do teste de Scott-Knott para essas características são apresentados na Tabela 3. Os maiores valores de DAP foram observados nos maiores espaçamentos (3,0 m x 2,0 m; 3,0 m x 2,5 m e 3,0 x 3,0 m) o que corrobora com os estudos realizados por Müller et al (2005b), Kirongo et al (2012) De modo geral, os resultados das pesquisas e plantios comerciais têm mostrado que o diâmetro é uma característica altamente responsiva aos espaçamentos, enquanto que os efeitos sobre a altura apresentam resultados controversos. Ocorrem casos onde a altura média das plantas aumenta com o aumento dos espaçamentos, e outros onde o resultado é inverso (Botelho, 1998).…”
Section: Primeira Rotaçãounclassified
“…But it is worth noting also that farmers need to get professional guidance especially as regards correct species/genotype selection and management, in particular spacing. For example, in a study of genotype and spacing effects on eucalypts growth, Kirongo et al (2012) report reduced growth for some genotypes and for closely spaced trees. Meanwhile, in another study, Kirongo et al (2013) reported that many farmers risked significant losses in investment arising from significant tree deaths as a result of intra-specific competition (between similar species) if trees were too crowded and recommended that farmers be advised 9.000,00 9.000,00 9.000,00 Table 7 Economic appraisal of a 5-year forestry venture with ucalyptus with no intermediate returns but under stringent economic scenario (doubled wages, land rent and management costs) e not to plant trees on their farms too closely.…”
Section: Investment Cost and Sell Prices Of Polesmentioning
confidence: 99%